Klasifikasi Tweets Masyarakat yang Membicarakan Layanan GoFood dan GoRide pada GoJek Dimedia Sosial Twitter Selama Masa Kenormalan Baru (New Normal) dengan Metode Naive Bayes - Alvian Akmal Nabhan; Bayu Rahayudi; Dian Eka Ratnawati (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Twitter is a social media that has long been used and is still a trend today. On Twitter, a lot of users write an opinion on something that is currently being discussed and becomes a trend topic. Early May 2020 the world was shaken by the presence of Coronavirus Disease-19 which causes all life in all parts of the world to be constrained, especially the government sector which has an impact on economic activity has decreased. In Indonesian, a lot of companies have gone bankrupt and must terminate the employment. At that time, the transportation sector companies were the most affected is GoJek online transportation which was successful as a unicorn start-up. GoJek was badly hit by the implementation of the PSBB in various regions. Therefor, the community grouped tweets for existing services on GoJek in social media twitter during the pandemic and new normal . In this study case, the GoJek services used are GoFood and GoRide using Naive Bayes classification model with testing using cross validation and confusion matrix. From this classification, good accuracy result are obtained by testin with 10-fold with mean accuracy 0,94, precission 0,73, recall 0,72 f-measure 0,72.